Adorasi Ekaristi sebagai Sacramentum Caritatis dalam Pendidikan Agama Katolik - Emiliana Vivi (Berkat : Jurnal Pendidikan Agama dan Katolik, 2026)
Studies on Eucharistic Adoration have predominantly emphasized its role as a personal devotional practice and individual spirituality, while its implications for Catholic Religious Education as a space for faith formation remain underexplored. This gap indicates the need for a theological-pedagogical reflection that connects Eucharistic Adoration with the process of faith education, particularly in the context of young people. This study aims to examine Eucharistic Adoration as an expression of Sacramentum Caritatis and its relevance as a formative space within Catholic Religious Education. The research employs a qualitative approach through a library research method, analyzing Church documents, theological works, and relevant academic literature on the Eucharist, faith education, and psycho-spiritual well-being. The findings reveal that Eucharistic Adoration is not merely a liturgical or devotional practice but also holds significant pedagogical value. It can be understood as a contemplative space that enables young people to experience a personal relationship with Christ, reflect on their inner experiences, and deepen their awareness of God’s transformative love. Furthermore, this study indicates that Eucharistic Adoration has the potential to support psycho-spiritual well-being by providing moments of silence, self-acceptance, and meaning-making in the light of faith. These findings highlight that integrating Eucharistic Adoration into Catholic Religious Education can enrich faith learning processes and help young people live their faith in a more personal and holistic manner. This study contributes to theological and educational discourse by positioning Eucharistic Adoration as a relevant practice of faith formation within contemporary Catholic education.